2020
DOI: 10.1101/2020.06.14.150466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human prefoldin modulates co-transcriptional pre-mRNA splicing

Abstract: Prefoldin is a heterohexameric complex conserved from archaea to humans that plays a cochaperone role during the cotranslational folding of actin and tubulin monomers. Additional functions of prefoldin in the cell nucleus have been described, including a positive contribution to transcription elongation and chromatin dynamics in yeast. Here we show that prefoldin depletion provoked transcriptional alterations across the genome of human cells. Severe pre-mRNA splicing defects were also detected, particularly un… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…This may occur, for instance, by facilitating the recruitment of the remodeler to the chromatin. Although PFDs do not seem to bind DNA directly, they have been found bound to the chromatin by ChIP in yeast and humans (Wang et al, 2017;Payán-Bravo et al, 2020;Millan-Zambrano et al, 2013), and by cell fractioning in Arabidopsis (Locascio et al, 2013). The molecular mechanism that provides specificity to PFDs' action on H2A.Z deposition is, therefore, a matter for future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may occur, for instance, by facilitating the recruitment of the remodeler to the chromatin. Although PFDs do not seem to bind DNA directly, they have been found bound to the chromatin by ChIP in yeast and humans (Wang et al, 2017;Payán-Bravo et al, 2020;Millan-Zambrano et al, 2013), and by cell fractioning in Arabidopsis (Locascio et al, 2013). The molecular mechanism that provides specificity to PFDs' action on H2A.Z deposition is, therefore, a matter for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Work in Arabidopsis has demonstrated that PFDs participate in the splicing of a particular set of pre-mRNAs by promoting the stability of the core spliceosome complex LSM2-8 (Esteve-Bruna et al, 2020). In humans, depletion of PFDN5 affects co-transcriptional splicing of long genes by preventing the recruitment of the splicing factor U2AF65 to the target loci (Payán-Bravo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%